2022
DOI: 10.3390/v14081612
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Diversity of Torque Teno Virus in Blood Samples from Febrile Paediatric Outpatients in Tanzania: A Descriptive Cohort Study

Abstract: Torque teno virus (TTV) is considered to be an ubiquitous member of the commensal human blood virome commonly reported in mixed genotype co-infections. This study investigates the genomic diversity of TTV in blood samples from 816 febrile Tanzanian children. Metagenomic next-generation sequencing was used to screen for TTV in individual blood samples from a cohort of 816 febrile Tanzanian paediatric outpatients. For positive samples, the number of TTV species and genotypes present were evaluated. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Overall, there were no false positives ( Table S1 ). Furthermore, SCANellome was evaluated on 10 blood samples of which we had previously analyzed and published the genomic diversity of TTV [ 17 ]. This comparative analysis shows the robustness of SCANellome, which successfully detected all of the TTV species reported in our previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there were no false positives ( Table S1 ). Furthermore, SCANellome was evaluated on 10 blood samples of which we had previously analyzed and published the genomic diversity of TTV [ 17 ]. This comparative analysis shows the robustness of SCANellome, which successfully detected all of the TTV species reported in our previous study.…”
Section: Methodsmentioning
confidence: 99%
“…It is known (and seems to be the rule) that a single individual (a child or adult) can be co-infected by a large number of different human anellovirus species and genotypes of the same genus [ 14 , 15 , 16 , 17 ]. We recently reported a significant trend toward an increase in TTV genomic diversity with age in a cohort of children under five years of age [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bile [11,12] Liver [13] Cervical [2] Bone marrow [12,13] Gut [14] Nasal [15] Fetal [16] Gastric [17] Placenta [16] Cervical lymph nodes [18] Blood [19] Saliva [20] Urine [21] Fecal [22] Sweat [23] Semen [20] Plasma [24] Breast milk [5] Amniotic fluid [25] Torque teno mini virus (TTMV) Bile [12] Liver [26] Cervical [2,27] Bone marrow [12] Brain [28,29] Gingival [30] Cervical lymph nodes [18] Blood [24] Saliva [24] Torque teno midi virus (TTMDV) Cervical [31] Nasopharyngeal [32] Blood [33] Urine [32] Stool [32] Kb, and the TTMV genome is 2.7 to 2.9 Kb [1,47]. TTV has diverse tissue tropism, and the virus genome has the ability to replicate simultaneously in several different tissues and organs, such as the liver, spleen, pancreas, bone marrow, muscle, lung, kidney, peripheral blood mononuclear cells (PBMC), etc [21,48].…”
Section: Torque Teno Virus (Ttv)mentioning
confidence: 99%
“…Torque teno virus (TTV) belongs to alphatorquevirus, torque teno mini virus (TTMV) belongs to betatorquevirus and torque teno midi virus (TTMDV) belongs to gammatorquevirus. The genome of these viruses is circular single-stranded, negative-sense DNA ranging from ∼2.0 to 3.9 kilobases (kb); the capsid of these viruses has icosahedron symmetry, and their total particle diameter is about 18 to 30 nm, and their nucleocapsid does not have a lipid envelope [1][2][3][4][5][6]. Human anelloviruses (AVs) are among the most common human viruses and are considered part of the human virome.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in next-generation sequencing (NGS) have deepened our knowledge on the microbial world. The combination of molecular biology technics like rolling circle amplification (RCA) with NGS on different human samples (both fluid and tissues) demonstrated that anelloviruses are one of the major components of the human virome, with TTV being one of the most prevalent viruses detected [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%